2018
DOI: 10.1186/s12879-018-2976-1
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation and simultaneous co-infection of dengue, chikungunya, and zika viruses in patients with febrile syndrome at the Colombian-Venezuelan border

Abstract: BackgroundIn Colombia, the dengue virus (DENV) has been endemic for decades, and with the recent entry of the chikungunya virus (CHIKV) (2014) and the Zika virus (ZIKV) (2015), health systems are overloaded because the diagnosis of these three diseases is based on clinical symptoms, and the three diseases share a symptomatology of febrile syndrome. Thus, the objective of this study was to use molecular methods to identify their co-circulation as well as the prevalence of co-infections, in a cohort of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(139 citation statements)
references
References 74 publications
2
124
0
8
Order By: Relevance
“…In which case it is also possible to consider that dengue's force of infection could influence its predominance in Latin America . However, given the nature of these studies, these findings are influenced by individual immunological status and a health seeking behaviour that has not been widely studied in our context , and therefore should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In which case it is also possible to consider that dengue's force of infection could influence its predominance in Latin America . However, given the nature of these studies, these findings are influenced by individual immunological status and a health seeking behaviour that has not been widely studied in our context , and therefore should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from our study, and other longitudinal studies [7,26], that as the epidemic moved through islands and countries it was the dominant cause of AFI for a period of 2-4 months. However, in both longitudinal and cross-sectional studies [7,26,27], what also emerges is a more complex picture of a mélange of arboviral infections, with frequent coinfections and cases and case clusters attributable to other viruses surrounding the CHIKV epidemic peak. In Haiti, in contrast to other studies that relied on serologic assays, we performed actual viral cultures on a majority of case patients; findings further underscored the extent of coinfections [19], and resulted in the identification of "unexpected" viruses, such as ZIKV and MAYV.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, Ae. aegypti can also be the main vector of other viruses, such as ZIKV and DENV, and co-transmission events may be observed (Carrillo-Hernández et al, 2018). However, it has been demonstrated that simultaneous infections by DENV/CHIKV/ZIKV or DENV/CHIKV in Ae.…”
Section: Historical and Epidemiological Aspectsmentioning
confidence: 99%
“…In addition, it is difficult to determine the frequency and intensity of the symptoms and correctly assess pain (mild, moderate and intense) of afflicted patients (Table 1). In this context, variations in the clinical presentation of cases can give hints as to the viral etiology; for instance, the salient and prolonged polyarthralgia, often accompanied by rash, is typically more indicative of chikungunya, while hemorrhagic manifestations and myalgia are more commonly observed in DENV infections (Lee et al, 2012) Despite the patients co-infected with CHIKV/DENV, CHIKV/ZIKV and CHIKV/DENV/ZIKV often do not show exacerbation of clinical signs, the co-infection presents as additional obstacle during differential diagnosis (Furuya-Kanamori et al, 2016;Villamil-Gómez et al, 2016;Carrillo-Hernández et al, 2018). Tables 1 and 2 summarize clinical and laboratory features that should be evaluated for efficient differential diagnosis of CHIKV, DENV and ZIKV infections.…”
Section: Differential Diagnosis Between Chikungunya Zika and Denguementioning
confidence: 99%